Highlighting an atypical cause of the Face of the Giant Panda sign - Vella, Stephanie (BJR Case Rep, 2017)
The “Face of the Giant Panda” and the “Panda Cub” signs are neuroimaging features originally described in patients with Wilson’s disease. We present a case with similar imaging findings in a different clinical context and highlight other differential diagnoses to be considered when presented with this particular radiological sign.